Mitofusin2, as a Protective Target in the Liver, Controls the Balance of Apoptosis and Autophagy in Acute-on-Chronic Liver Failure - Xue, Ran; Yang, Jing; Jia, Lin; Zhu, Xuemin; Wu, Jing; Zhu, Yueke; Meng, Qinghua (Frontiers in Pharmacology, 2019)
Aim Acute-on-chronic liver failure (ACLF) is closely related to mitochondrial dysfunction. Previous studies showed the vital role of mitofusin2 (Mfn2) in the regulation of mitochondrial function. However, the effect of Mfn2 on ACLF remains unknown. As one of mitochondrial-related pathways, BNIP3-mediated pathway controls the balance between apoptosis and autophagy. However, the relationship between Mfn2 and BNIP3-mediated pathway in ACLF is still obscure. The aim of our study is to clarify the effect of Mfn2 and potential molecular mechanisms in ACLF. Methods We collected liver tissue from ACLF patients and constructed an ACLF animal model and a hepatocyte autophagy injury model, using adenovirus and lentivirus to deliver Mfn2 and Mfn2-siRNA to liver cells, in order to assess the effect of Mfn2 on autophagy and apoptosis in ACLF. We explored the biological mechanisms of Mfn2-induced autophagy and apoptosis of ACLF through western blotting, RT-PCR, transmission electron microscopy, immunofluorescence, immunohistochemical staining and Hematoxylin-Eosin staining. Results Compared with the normal liver tissue, the expressions of Mfn2, Atg5, Beclin1 and LC3-II/I were significantly decreased and the expression of P62 was much higher in patients with ACLF. Mfn2 significantly attenuated ACLF, characterized via microscopic histopathology and reduced serum AST and ALT levels. Mfn2 promoted the expressions of ATP Synthase β, Atg5, Beclin1, LC3-II/I and Bcl2 and reduced the expressions of P62, Bax and BNIP3. Conclusions Mfn2 plays a protective role in the progression of ACLF. BNIP3-mediated signaling pathway is not the only factor associated with Mfn2 controlling the balance of apoptosis and autophagy in ACLF. Mfn2 will provide a promising therapeutic target for patients with ACLF.